Implicit Self-Esteem: Nature, Assessment and Role in Psychopathologies - İmamoǧlu, Ahmet Hamdi; Bilge, Yız (Psikiyatride güncel yaklaşimlar, 2021)
Many methods have been developed in which self-related stimuli are presented to measure implicit self-esteem. [...]a new variable that can play a critical role in contexts such as personality, interpersonal relationships, and psychopathology has been defined in the literature on self-esteem, which is generally based on findings measured by self-reporting. [...]it has been observed that implicit self-esteem can play a central role in psychopathologies both in terms of its relation to explicit self-esteem and independently from it, however, studies on the subject have revealed inconsistent findings in some areas. [...]Brown and Marshall (2006) indicates that the concept is used at least in three different ways, which are a) as a personality variable that expresses the way people feel about themselves as a whole; (b) as self-evaluative reactions that arise in relation to certain experiences; (c) as perception of self-competence in different contexts. [...]the concept of self-esteem is handled as a one-dimensional structure loyal to its origin, while different components such as contingent and noncontingent, stable and unstable, global and domain-specific, also defined (Abdel-Khalek 2016). [...]many studies conducted in different cultures and different samples, it is observed that individuals' implicit attitudes towards self-related stimuli tend to be positive (Greenwald and Farnham 2000, Dunham et al. 2007, Falk et al. 2009, Vater et al. 2013).